The impact of hard winters on waterfowl populations of south Sweden - Nilsson, Leif (Wildfowl, 1984)
This paper tries to evaluate the possible influence of hard winters on the populations of waterfowl wintering (at least partly) in the Baltic on the basis of the international midwinter counts (1967-1983) and September counts (1973-1982) undertaken in south Sweden. Three especially cold winters occurred (1970, 1979, 1982). During the study period most species showed increasing tendencies in the winter indices although the increases ended with the 1979 winter for some species. The hard winters had a marked effect on the populations of some wintering species, being most marked in Coot Fulica atra that decreased by 80% after the 1979 winter. In general the least efficient divers experienced the most marked reductions after hard winters. The variability in the indices showed the same relation to diving ability. Winter conditions and especially the availability of winter food can be a regulatory factor for several species of waterfowl wintering in northern areas. During normal winters the food resources are sufficient for much larger populations, but the ice will impose serious limits to the available food resources.